1964
DOI: 10.1037/h0044107
|View full text |Cite
|
Sign up to set email alerts
|

Differences in visual perception and in visual-motor functioning between psychotic and nonpsychotic children.

Abstract: The writer wishes to express her thanks to the members of her Dissertation Committee, Laurance F. Shaffer, Rosedith Sitgreaves, Joel R. Davitz, and, most especially, the chairman of the committee, Edward J. Shoben, Jr., for their steady guidance, assistance, and encouragement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1972
1972
1983
1983

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…However when Safrin (1964) attempted to validate this thesis, he failed to find signs of such a maturational lag in his psychotic subjects. Mahler (1952), in an earlier discussion of a condition which she labelled &dquo;symbiotic child psychosis,&dquo; had also postulated maturational lag.…”
mentioning
confidence: 79%
“…However when Safrin (1964) attempted to validate this thesis, he failed to find signs of such a maturational lag in his psychotic subjects. Mahler (1952), in an earlier discussion of a condition which she labelled &dquo;symbiotic child psychosis,&dquo; had also postulated maturational lag.…”
mentioning
confidence: 79%
“…Several studies have explored the effects of intelligence and of organicity on the Bender responses of schizophrenic children. Goldberg (1957) found a significant correlation between Bender scores and IQ for retarded children 11-16 years of age, but not for a matched group of schizophrenics; but Safrin (1964) found a strong relationship between level of visual motor functioning and mental age in both schizophrenic and normal children. Safrin found no relationship between Bender scores and the presence or absence of neurological deficits, and McConnell (1967) found that Koppitz developmental scores for the Bender were related to various levels of organicity and that nonorganic psychotics were undifferentiated from children with minimal levels of organicity.…”
mentioning
confidence: 99%